THE PRODUCTIVITY OF FIELD CROP ROTATION UNDER POTASSIUM DEFICIENT FERTILIZATION SYSTEM - Hospodarenko H. М.; Martyniuk A. Т.; Boiko V. Р. (Scientific Progress & Innovations, 2021)
The study results of the effect of long-term (8 years) using potassium deficient fertilization system on changing the parameters of physical, chemical and agrochemical indicators of podzolized heavy loam black soil and the productivity of field crop rotation (winter wheat, corn, spring barley, soybean) are presented. The study was held in the Right-Bank Forest-Steppe of Ukraine. It has been established that, under all agro-chemical loads, the soil absorbing complex capacity does not change, but its structural reorganization takes place. Before starting the experiment, the soil absorbing complex capacity in the 0–20 cm layer was deter-mined by 10.1 % hydrogen ions, and eight years later, under the average annual application of N110P60K80, their share increased to 14.8 %. In the variants with the potash fertilizers application, the deterioration of these indicators increased. Potassium regime of the soil depended on the types and rates of fertilizers used in crop rotation. It was most affected by rates of potash fertilizers. On the areas without fertilizers at the end of the second year of four-field crop rotation, the content of labile potassium compounds in the soil decreased by 6 % as compared with the initial value, and at applying N110P60, N110P40 and N110P60K80 per 1 ha of crop rotation area it decreased by 14; 5 and 3%, respectively. Long-term (since 2010) application of mineral fer-tilizers at a dose of N110P60K80 per 1 ha of crop rotation area, in 2016–2018 contributed to an increase in winter wheat yield by 3.68 t/ha, corn by 8.34, spring barley by 2.05 and soybeans by 1.31 t/ha, while the yields on control areas without fertilizers, made 3.57 t/ha; 4.73; 3.37 and 1.71 t/ha, respectively. Moreover, potash fertilizers at nitrogen-phosphorus background at a dose of 40 kg/ha contributed to an increase in the yields of winter wheat, corn, spring barley and soybean by 7, 12; 5 and 3 %, respectively, and the crop rota-tion productivity rose by 8 %. A further increase in the dose of potash fertilizers to 80 kg/ha improved its productivity by only 4 %. To ensure the productivity of field crop rotation at the level of 7.55 tons/ha, it is necessary to apply potash fertilizers at a dose of 40 kg/ha (for winter wheat 40, corn ‒ 55, spring barley ‒ 35 and soybean ‒ 30) annually against the background of N110P60 and plow non-marketable parts of the harvest into the ground.